Schoolboy's Mate - Averkieva, Olga. (Russia, 2016)
6-years old Dima lives 2 days with his dad and 2 days with his mom by turns, because his parents are divorced. Every one of them strives for his own perfect type of educating their son. But what does Dima himself strive for?
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films